Significance of genetic polymorphisms in long non-coding RNA AC079767.4 in tuberculosis susceptibility and clinical phenotype in Western Chinese Han population - Zhenzhen Zhao (Nature Portfolio, 2017)
Abstract Recent studies have implicated long non-coding RNA, AC079767.4, as a highly susceptible gene in tuberculosis. The aim of the study was to preliminarily explore the possible association of single nucleotide polymorphisms (SNPs) in AC079767.4 gene with clinical phenotypes and TB susceptibility in Western Chinese Han population. The improved multiplex ligation detection reaction (iMLDR) method was employed to genotype 4 SNPs in AC079767.4 in 554 tuberculosis patients and 561 healthy individuals. In subgroup analysis, only the C allele for rs12477677 was associated with the decreased susceptibility to pulmonary TB with a p-value of 0.026, but p-value was 0.103 after Bonferroni correction. In total samples, haplotype [ACAC], representing four AC079767.4 variants, was found to slightly decrease TB risk (p = 0.045). Furthermore, patients with the CC genotype of rs12477677 were correlated with fewer occurrences of fever (p = 0.016), while patients carrying the T allele were associated with lower levels of ESR in the dominant model of rs1055229 (p = 0.021). For the first time, we reported the potential susceptibility and clinical traits of tuberculosis with lncRNA variants in the Western Han Chinese population. Our data indicate AC079767.4 polymorphisms may potentially act as novel biomarkers for tuberculosis diagnostic and therapeutic purposes.